Pemanfaatan Mobile Application Si-Apik bagi Perempuan Pesisir Pelaku Usaha Sektor Pariwisata Maritim - Manafe, Mesri Welhelmina Nisriani; Fanggidae, Herny Constantia; Imelda Seseli, Eka Merdekawati; Fanggidae, Frits Oscar (LP2M INSURI Ponorogo, 2023)
Covid-19 pandemic and Tropical Cyclone Seroja have had a negative impact on MSMEs in the tourism sector in Kupang City. The closure of tourist sites resulted in a decrease in the family's economic capacity. This phenomenon is agreed in priority issues of partners who are unable to measure their financial ability to deal with business uncertainty which then has an impact on low access to capital. The aim of PKM is to empower business actors to be able to maintain their business in order to improve the family economy. Empowerment of management aspects using the PRA method through Secondary Data Collection, Focus Group Discussion (FGD) and Participatory Modeling Mapping and implementation stages through outreach, training/simulation and mentoring as well as evaluating the use of the SI-Apik application and ultra-micro financing for tourism businesses in Lasiana City Beach Kupang. Partners are 5 housewives who have been running the business for more than 10 years. The analysis results showed an increase in understanding, knowledge, ability, and skills in utilizing financial applications between >50%-100% for 5 indicators and 20%-40% for 4 achievement indicators. Ultra micro financing activities reach ≥80%.